Analyse de la dynamique de l'offre de noix brutes de cajou en Côte d’Ivoire : une application par l’approche autorégressif à retards échelonnés (ARDL) - Ouattara Gniré Mariam (European Scientific Journal, ESJ, 2018)
This article examines the factors influencing the long-term supply of cashew nuts in Côte d'Ivoire. Using a co-integration model based on the ARDL (Self-regressive with Staggered Delay) approach, the study explains a long-term relationship between cashew supply and explanatory factors of production dynamics. In the long term, an increase in the field price of cashew causes an increase in production of 0.42%. Similarly, a 1% increase in exports and cultivated areas lead to an increase of 0.91% and 0.18%, respectively, in the supply of raw cashew nuts.